2013
DOI: 10.1097/acm.0b013e3182a2e30d
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Spanish Use and Language Proficiency Testing Among Pediatric Residents

Abstract: Regardless of level of Spanish proficiency, pediatric residents provide clinical care to patients in Spanish. Self-reported Spanish proficiency does not reliably predict tested ability, especially when using stringent criteria to define proficiency. Provider language "credentialing" is an important step in implementing a policy to improve care for limited English proficiency patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…While some prior data suggests that learners may overestimate language fluency skills prior to being exposed to learning or testing the material [14], our data suggests that a robust extended-duration faculty-led course with opportunities for simulated formative assessment enables students to reach a balanced and informed understanding of their own language skill set in a medical context, and to sustain these skills into residency.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…While some prior data suggests that learners may overestimate language fluency skills prior to being exposed to learning or testing the material [14], our data suggests that a robust extended-duration faculty-led course with opportunities for simulated formative assessment enables students to reach a balanced and informed understanding of their own language skill set in a medical context, and to sustain these skills into residency.…”
Section: Discussionmentioning
confidence: 63%
“…Self-evaluation has been previously used as a means for rating students’ ability to determine comfort level and preparedness to interview Spanish-speaking patients or caregivers [12, 13], though in the absence of formal Medical Spanish exposure and assessment may have limited accuracy [1416]. …”
Section: Introductionmentioning
confidence: 99%
“…21,22 At the encounter level, provider decision-making includes considerations of their own and the patient's or family's language proficiency, convenience, and the expected complexity of the clinical encounter. [23][24][25] Unfortunately, clinicians do not reliably assess their own proficiency, 24 and a priori decisions about an encounter's complexity necessarily account only for the clinician's agenda, not the family's. In addition, some families, not accustomed to being offered professional interpretation, bring untrained friends or family members to interpret.…”
mentioning
confidence: 99%
“…Past work has shown that pediatric providers at academic institutions conducted visits without interpreters even if they did not rate their Spanish language skills as proficient. 21 A study from the adult literature reported similar findings, describing that physicians conduct visits in their second language, even when limited in fluency, to save time, for convenience, and as a chance to improve their language skills. 22 Therefore, provider competency in languages other than English should be seen as a formally taught and tested professional skill, replacing the traditional approach that has allowed and even encouraged providers to just “get by” with unmeasured language proficiency.…”
Section: Introductionmentioning
confidence: 78%